The Case for TAAR1 as a Modulator of Central Nervous System Function - Rutigliano, Grazia; Accorroni, Alice; Zucchi, Riccardo (Frontiers in Pharmacology, 2018)
TAAR1 is widely expressed across the mammalian brain, particularly in limbic and monoaminergic areas, allegedly involved in mood, attention, memory, fear, and addiction. However, the subcellular distribution of TAAR1 is still unclear, since TAAR1 signal is largely intracellular. In vitro, TAAR1 is activated with nanomolar to micromolar affinity by some endogenous amines, particularly p-tyramine, beta-phenylethylamine, and 3-iodothyronamine (T1AM), the latter representing a novel branch of thyroid hormone signaling. In addition, TAAR1 responds to a number of psychoactive drugs, i.e. amphetamines, ergoline derivatives, bromocriptine and lisuride. Trace amines have been identified as neurotransmitters in invertebrates, and they are considered as potential neuromodulators. In particular, beta-phenylethylamine and p-tyramine have been reported to modify the release and/or the response to dopamine, norepinephrine, acetylcholine and GABA, while evidence of cross-talk between TAAR1 and other aminergic receptors has been provided. Systemic or intracerebroventricular injection of exogenous T1AM produced prolearning and antiamnestic effects, reduced pain threshold, decreased non-REM sleep, and modulated the firing rate of adrenergic neurons in locus coeruleus. However each of these substances may have additional molecular targets, and it is unclear whether their endogenous levels are sufficient to produce significant TAAR1 activation in vivo. TAAR1 knock out mice show a worse performance in anxiety and working memory tests, and they are more prone to develop ethanol addiction. The also show increased locomotor response to amphetamine, and decreased stereotypical responses induced by apomorphine. Notably, human genes for TAARs cluster on chromosome 6 at q23, within a region whose mutations have been reported to confer susceptibility to schizophrenia and bipolar disorder. For human TAAR1, around 200 non-synonymous and 400 synonymous single nucleotide polymorphisms have been identified, but their functional consequences have not been extensively investigated yet. In conclusion, the bulk of evidence points to a significant physiological role of TAAR1 in the modulation of central nervous system function and a potential pharmacological role of TAAR1 agonists in neurology and/or psychiatry. However, the specific effects of TAAR1 stimulation are still controversial, and many crucial issues require further investigation.